Phytochemical and Antibacterial Evaluation of Pterygota Alata Leaf Extracts Against CSOM Bacteria - Singhsamanta, Debidatta; Rath, Shakti; Das, Saumya Ranjan (Al-Nahrain Journal of Science, 2025)
The increasing rates of multidrug-resistant (MDR) organisms among patients with chronic suppurative otitis media (CSOM) have caused treatment procedures to become more complex, raising healthcare costs and significantly increasing the time of recovery. Since medicinal plants are the natural repositories for bio-active and secondary metabolites, they are an excellent alternative to antibiotics to combat MDR bacterial strains. This study aims to assess the antibacterial activity and the presence of phytochemicals in the aqueous and methanol leaf extracts of the Indian deciduous tree Pterygota alata against 5 MDR strains of CSOM-causing bacteria: Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli, Proteus mirabilis, and Klebsiella pneumoniae. Fresh P. alata leaves were harvested, dried, and extracted with methanol and water. Qualitative and quantitative assessments demonstrated the detection of primary and secondary metabolites. The antibacterial activities were determined using the agar well diffusion method, including minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), dose-response, and time-kill studies against CSOM bacterial isolates. Most phytochemicals, except proteins, were present in moderate to high concentrations in aqueous and methanol extracts. The methanol extracts had higher levels of phenolics (85.6 mg/g), flavonoids (42.3 mg/g), tannins (40.8 mg/g), and saponins (36.9 mg/g). Steroids were minimal in both extracts, while alkaloids were moderately present. All extracts showed significant antibacterial activity, particularly the methanol extracts against S. aureus and P. mirabilis (ANOVA, p ≤ 0.05). The effect was concentration-dependent, with rapid bactericidal action observed at higher concentrations. It was further confirmed with one-way ANOVA followed post-hoc Tukey test, there were significant differences among different treatments (p ≤ 0.05), supporting the reliability of the results. Therefore, it can be concluded from this study that methanolic leaf extracts of P. alata can be used as an alternative or complementary antibacterial agent against MDR CSOM infections.